096 Assessment of the efficacy of erenumab during the open-label treatment (13–24 weeks) of subjects with episodic migraine who failed 2–4 prior preventive treatments: results of the LIBERTY study. (29th July 2019) - Giles, Lauren; Reuter, Uwe; Goadsby, Peter; Lanteri-Minet, Michel; Hours-Zesiger, Peggy; Fernandes, Chrystel; Ferrari, Michel; Klatt, Jan
Abstract : Introduction: To assess efficacy of erenumab in the first three months of the open-label extension phase (OLEP; 13–24 weeks) of the LIBERTY study. Methods: In the double-blind treatment phase (DBTP), 246 patients were randomized to placebo and erenumab 140 mg for 12 weeks, following which, patients completing that phase (N=240) were enrolled in OLEP, to receive monthly erenumab 140 mg. Outcomes measured monthly throughout to week 24 were achievement of at least 50%/75%/100% reduction in monthly migraine days (MMD), change from DBTP baseline in MMD, monthly acute migraine-specific medication days (MSMD), Headache Impact Test (HIT-6TM) total score, everyday activities (EA) and physical impairment (PI) as measured by the Migraine Physical Function Impact Diary (MPFID). Results: Overall, 228/240(95.0%) patients completed the 24 week visit of the OLEP. In the overall population at Week 24, 39.2%, 15.9% and 7.0% patients achieved ≥50%/≥75%/100% reduction in MMD. The mean (standard deviation) change from DBTP baseline in MMD was −2.7(4.4) and −1.4(3.0) in MSMD; and −7.6(8.0), −2.5(9.2) and −4.0(9.0) in HIT-6TM, MPFID-PI and MPFID-EA scores respectively. Patients with continuous use of erenumab showed sustained efficacy in all outcomes assessed. Patients who switched from placebo to erenumab in the OLEP showed improvement from the first measurement at Week 16 on all outcomes assessed. Conclusions: Efficacy of erenumab was sustained throughout 24 weeks in a hard to treat patient population with multiple prior preventive treatment failures. Overall, efficacy data over 24 weeks (assessed over weeks 13–16, 17–20 and 21–24) was generally in line with prior erenumab trials.